Analysis of the Role of Regional Governments on Inclusive Growth (Macroeconomic Approach Study ) - Setyowati RN, Wahyu Retno; Santoso, Dwi Budi; Ekawaty, Marlina (Institute of Research and Community Service, University of Brawijaya, 2021)
Abstract: Development is a multidimensional process that involves changes in social structure, which are based on the main orientation: the occurrence of economic acceleration, the reduction of inequality, and yet, the problem of poverty and unemployment remains an unresolved problem of absolute poverty reduction. Development also aims to achieve sustainable and inclusive economic growth. On the other hand the problem of poverty and unemployment remains as an unresolved issue. So it is necessary for the role of government, both local and central government, where the government is a driver and a planner of development. The goal is to eliminate three issues: unemployment, distribution inequality, and poverty, so that development outcomes can be enjoyed by the community fairly and evenly / inclusively. This study aims to find out which government spending can accelerate inclusive growth. This research used panel data method with simultaneous equation 3 stage least square. The results showed that capital expenditure had a negative effect on economic growth, while employee salary and population growth rate did not affect the economic growth. Capital expenditures, staff salaries, economic growth, and human development index affect the open unemployment rate. The open unemployment rate affects poverty, while economic growth has no effect on poverty.Key Words: Inclusive growth, local government spending, unemployment, and poverty.Â